Social Capital as Protection Against the Mental Health Impact of the COVID-19 Pandemic - Snel, Erik; Engbersen, Godfried; de Boom, Jan; van Bochove, Marianne (Frontiers in Sociology, 2022)
The corona pandemic has a huge impact on the mental well-being of the Dutch population. Based on a large-scale panel survey (N=22,696) on the social impact of COVID-19, this article firstly examines which social groups are most susceptible to the mental health consequences of the pandemic. Secondly, we examine whether social capital provides protection against this impact. We find that the mental health consequences of COVID-19 are considerable and increased over the course of 2020. Women, young people, respondents with low incomes and/or poor self-perceived health, experience relatively more fear and stress due to the virus. We do not find a difference between respondents with or without a migration background. Social capital (received support, trust in people and in institutions) has the expected effect: the more support and trust, the less fear and stress. There is a mediation effect. Older people, respondents with high incomes and/or good health experience less fear and stress, partly because they have more social capital. This is different for females. They would experience even more fear and stress, compared to men, were it not for the fact that they have more social capital. Hence we conclude that social capital indeed provides some protection against the negative mental health consequences of COVID-19.